2009
DOI: 10.1007/s10597-009-9199-2
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Adequacy and Work Status Among Medicaid Enrollees with Disabilities: A Restriction-based, Propensity Score-adjusted Analysis

Abstract: This cross-sectional study of adult survey respondents with disability and depression (n = 199) enrolled in Massachusetts' Medicaid program examined the association of adequately or inadequately prescribed antidepressant treatment and self-reported work status using conditional logistic regression, controlling for age, gender, race, marital status, education, receipt of SSI/SSDI, self-reported disabling condition, and health status. Confounding by severity was addressed by two methods: restriction of our sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
(26 reference statements)
1
14
0
Order By: Relevance
“…Similar findings were reported by Burton, Chen, Conti, Schultz, and Edington (2007) who found that adherence to antidepressant medication was associated with a decreased likelihood of filing short-term disability claims. Simon et al (2001) and Smith, Henry, Zhang, Hooven, and Banks (2009) confirmed these findings. Such data could make a useful basis for developing and evaluating programmes.…”
Section: Mental Health Interventionssupporting
confidence: 71%
“…Similar findings were reported by Burton, Chen, Conti, Schultz, and Edington (2007) who found that adherence to antidepressant medication was associated with a decreased likelihood of filing short-term disability claims. Simon et al (2001) and Smith, Henry, Zhang, Hooven, and Banks (2009) confirmed these findings. Such data could make a useful basis for developing and evaluating programmes.…”
Section: Mental Health Interventionssupporting
confidence: 71%
“…The heterogeneity of the algorithms across the studies constrains strict comparisons. For example, the study that defined depression on the basis of at least two outpatient or one inpatient codes for depression (296.2, 296.3, 300.4, and 311) in a 12‐month period likely included a narrower patient population than did the study that required only a single depression claim (296.2, 296.3, and 311) …”
Section: Resultsmentioning
confidence: 99%
“…Five studies focused exclusively on populations with specific conditions including diabetes, asthma, and disability . Of the other six studies, two were limited to patients who had received inpatient treatment, and one was limited to veterans and focused on new onsets of depression .…”
Section: Resultsmentioning
confidence: 99%
“…These codes have been used previously and exclude bipolar disorder, schizoaffective disorder, and dysthymic disorder. 8,11,22,2628 Presence of depression was defined as at least one diagnosis code on at least 1 inpatient claim or 2 outpatient claims during the study period. To be included in our study cohort, we required a diagnosis of depression at least once following initial COPD diagnosis.…”
Section: Methodsmentioning
confidence: 99%